PERAN PENDIDIKAN ISLAM DALAM MEMELIHARA KEBERAGAMAN BUDAYA DAN IDENTITAS KOLEKTIF - Ahmad Jamal; Acep Rahmat Acep Rahmat; Muhammad Ihda Hidayatur Ramadan; Muhammad Sulaiman Al-Muzzamil (Yayasan Al-Afif, 2024)
This study aims to understand the role of education in preserving cultural diversity and group identity. The research employs a literature review method, gathering research sources from articles, journals, and books relevant to the topic of discussion. The findings reveal that Islamic education plays a crucial role in addressing several issues, such as juvenile delinquency and crimes committed by minors, as these problems significantly impact social life. Therefore, one solution to these challenges is through multicultural education, specifically the